2005
DOI: 10.1007/s00221-005-0188-6
|View full text |Cite
|
Sign up to set email alerts
|

Glial reactions in a rodent cauda equina injury and repair model

Abstract: In the adult rat, an avulsion injury of lumbosacral ventral roots results in a progressive and pronounced loss of the axotomized motoneurons. A subsequent acute implantation of an avulsed ventral root into the spinal cord has neuroprotective effects. However, it has not been known whether a surgical implantation of an avulsed ventral root into the spinal cord for neural repair purposes affects intramedullary glial and microglial reactions. Here, adult female Sprague-Dawley rats underwent a unilateral L5-S2 ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…The finding that Pre084 treatment significantly prevented MN death prompted us to analyze its possible effects on glial cell reactivity that is associated with MN loss following root avulsion Ohlsson et al, 2006;Penas et al, 2009). Despite that it has been shown that activation of Sig-1R and Sig-2R by agonists with the same affinity for both receptors suppresses microglial activation in vitro (Hall et al, 2009), we did not observe changes in microglia immunoreactivity by Pre084 treatment at 0.25 mg/kg in vivo.…”
mentioning
confidence: 63%
“…The finding that Pre084 treatment significantly prevented MN death prompted us to analyze its possible effects on glial cell reactivity that is associated with MN loss following root avulsion Ohlsson et al, 2006;Penas et al, 2009). Despite that it has been shown that activation of Sig-1R and Sig-2R by agonists with the same affinity for both receptors suppresses microglial activation in vitro (Hall et al, 2009), we did not observe changes in microglia immunoreactivity by Pre084 treatment at 0.25 mg/kg in vivo.…”
mentioning
confidence: 63%
“…In all of the studies just mentioned, however, sensory afferent damage was inherent to the models being examined. We previously showed that reactive astrocytes, microglia, and macrophages are prominent in the ventral horn at the level of injury after VRA and VRA+Imp, and speculated that their presence was a direct result of neuronal injury (Ohlsson et al, 2006). We now show for the first time that an L6-S1 VRA injury results in significant activation of astrocytes, microglia, and macrophages in the ipsilateral deep dorsal horn gray matter and in the dorsal funiculus of the spinal cord segment immediately rostral to the level of injury, relative to Lam control levels, in spite of the absence of a direct injury to the primary afferents.…”
Section: A Motor Lesion Can Induce Sensory Plasticity Beyond the Levementioning
confidence: 99%
“…Although we have extensively examined autonomic and motoneuron cell death (Hoang et al, 2003), as well as inflammation (Ohlsson et al, 2006) in the ventral horn at the level of injury in this model, it is unknown whether VRA alters the processing of sensory information in the dorsal horn at or beyond the injured segment. As neuropathic pain is a consequence of this type of spinal cord injury in the clinical setting, we propose that the VRA injury may contribute to the development of neuropathic pain.…”
Section: Introductionmentioning
confidence: 99%
“…In line with our results, Brännström et al 30 demonstrated that the neuronal size of adult cat motoneurons is decreased by 29% at 12 weeks after permanent axotomy.Thus, although axotomy has no effect on the survival of the corresponding spinal motoneurons, cell atrophy, synaptic shedding, degeneration of dendrites and activation of microglia is induced, which also is the case following VRA. However, in contrast to the survival rate of motoneurons, an acute implantation of an avulsed root does not significantly affect the activation of glial cells in the ventral horn21 .The molecular mechanisms behind injury induced motoneuron degeneration are not understood, although it appears that trophic factor deprivation8,33 and nitric oxide-mediated oxidative stress 9 is of critical value. Spinal motoneurons express nitric oxide synthase (NOS) after VRA, in contrast to after ventral root transection 9 , where the motoneuron loss can be reduced by inhibition of NOS 10 .…”
mentioning
confidence: 99%